2014
DOI: 10.3136/fstr.20.317
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Simultaneous Detection Method for Foodborne Pathogens Using Surface Plasmon Resonance Biosensors

Abstract: Surface plasmon resonance (SPR) biosensors were used to develop a rapid and simultaneous detection method for three important foodborne pathogens, i.e., Escherichia coli O157:H7 (O157), Salmonella Enteritidis (SE), and Listeria monocytogenes (LM). Bacterial homogenates prepared by sonication from bacterial suspensions at variouscell concentrations were analyzed using SPR biosensors and sensor chips with polyclonal antibodies specific to each of the target pathogens. The precipitates from the homogenates were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
(32 reference statements)
1
16
0
Order By: Relevance
“…The surface of Sensor Chip was modified by the methods published previously (Zhang and others ). In brief, the gold surface of Sensor Chip Au (GE Healthcare Bio‐Sciences AB and Kyushu Keisokki Co., Ltd.) was cleaned and subsequently modified with the formation of a self‐assembled monolayer (SAM) by immersing in ethanol with 0.1 mM carboxy‐EG 6 ‐undecanethiol (PEG6; DOJINDO Laboratories, Kumamoto, Japan) and 0.9 mM hydroxy‐EG 3 ‐undecanethiol (PEG3; DOJINDO Laboratories) for 24 h at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The surface of Sensor Chip was modified by the methods published previously (Zhang and others ). In brief, the gold surface of Sensor Chip Au (GE Healthcare Bio‐Sciences AB and Kyushu Keisokki Co., Ltd.) was cleaned and subsequently modified with the formation of a self‐assembled monolayer (SAM) by immersing in ethanol with 0.1 mM carboxy‐EG 6 ‐undecanethiol (PEG6; DOJINDO Laboratories, Kumamoto, Japan) and 0.9 mM hydroxy‐EG 3 ‐undecanethiol (PEG3; DOJINDO Laboratories) for 24 h at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…In a study aimed at the rapid and simultaneous detection of L. monocytogenes and three food pathogens with surface plasmon resonance (SPR) biosensors, by analyzing the homogenates prepared from sonication of suspensions of different concentrations of pathogens using with SPR biosensors and sensor chips produced by polyclonal antibodies spesific to the pathogens, it was concluded that the working with the precipitates obtained from the centrifugation of homogenates increased the detection sensitivity and reported that the lower detection limit of L. monocytogenes may be 0.7×10 7 cfu/ml if the detection from precipitates with a multichannel SPR biosensor is carried out, even if non-target pathogens are at concentrations of 10 5 -10 8 cfu/ml (Zhang et al 2014).…”
Section: Surface Plasmon Resonance Based Biosensorsmentioning
confidence: 99%
“…It can also be used for the installation of immunosensors applied in the detection of food pathogens in various foods or food dilutions [60]. SPR was used for the detection of E. coli O157:H7, S. enteritidis, and L. monocytogenes by Zhang et al [6]. The lower detection limits for E. coli O157:H7, S. enteritidis, and L. monocytogenes were determined to be 0.6 × 10 6 , 1.8 × 10 6 and 0.7 × 10 7 CFU/mL, respectively, in the presence of nontarget pathogens at concentrations of 10 5 -10 8 CFU/mL.…”
Section: Fluorescence Resonance Energy Transfer-based Biosensorsmentioning
confidence: 99%
“…These methods have some advantages such as being informative, highly repeatable and possess the potential to combine detection, effectively identify, and quantify an unlimited number of foodborne pathogens in a single experiment. However, expensive equipment for array scanning and data collection are needed in this method [5,6].…”
Section: Introductionmentioning
confidence: 99%